Long‐distance nitrate signaling displays cytokinin dependent and independent branches. Issue 3 (23rd February 2016) - Ruffel, Sandrine; Poitout, Arthur; Krouk, Gabriel; Coruzzi, Gloria M.; Lacombe, Benoit
Summary: The long‐distance signaling network allowing a plant to properly develop its root system is crucial to optimize root foraging in areas where nutrients are available. Cytokinin is an essential element of the systemic signaling network leading to the enhancement of lateral root proliferation in areas where nitrate is available. Here, we explore more precisely: (i) which particular traits of lateral root growth (density and length of emerged lateral roots) are the targets of systemic signaling in a context of heterogeneous nitrate supply; and (ii) if the systemic signaling depends only on cytokinin or on a combination of several signalings. Abstract : Heterogeneous nutrient availability is frequent during plant life cycle. Therefore, long‐distance communication is crucial to properly tune root development according to local nutrient availability and whole‐plant needs. Here, we show that multiple traits of root development are the targets of nitrate long‐distance signaling, dependently or independently of cytokinin biosynthesis.